Donate Speech: Collecting and Sharing a Large-Scale Speech Database for Social Sciences, Humanities and Artificial Intelligence Research and Innovation - Lindén Krister; Jauhiainen Tommi; Lennes Mietta; Kurimo Mikko; Rossi Aleksi; Kurki Tommi; Pitkänen Olli. (De Gruyter, 2025)
The Donate Speech campaign aimed to collect 10,000 hours of ordinary, casual Finnish speech to be used for studying language as well as for develop-ing technology and services that can be readily used in the languages spoken in Finland. In this project, particular attention has been devoted to allowing for both academic and commercial use of the material. Even though this ambitious target currently seems likely to evade us, the Donate Speech campaign has managed to amass an extensive resource of more than 4,000 hours of Finnish colloquial speech comprising more than 220,000 speech recordings by more than 25,000 speakers from all over Finland in just a few months.
Keywords: speech resources, colloquial speech, large-scale data collection, aca-demic and commercial use
CLARIN: The Infrastructure for Language Resources